Legal Policy In The Formation Of The Omnibus Law On Job Creation In Indonesia - Ahmad; Ariawan Rahmat (International Conference On Law And Social Sciences, 2024)
This article aims to investigate the legal politics related to the formation of the Job Creation Omnibus Law in Indonesia, as well as analyzing the problems and challenges. The Omnibus Law was initiated as a strategic step in efforts to reform law and increase Indonesia's economic competitiveness. The research method used is normative legal research with a descriptive and evaluative analysis approach to the legal basis, formation process and in impact of the Job Creation Omnibus Law on society and the economy. The research results show that the Job Creation Omnibus Law has the main objective of simplifying regulations, encouraging investment, and reducing bureaucratic obstacles in order to increase economic growth. However, the implementation of this Law faces a number of problems which include legal uncertainty, inadequate labor protection, and potentially detrimental environmental impacts. The discussion identified several main challenges faced in the process of forming and implementing the Omnibus Law on Job Creation, including resistance from various parties including labor unions, concerns regarding loss of workers' rights, as well as complexity in drafting regulations which could give rise to ambiguity and conflicts of interpretation.